A mixed-methods examination of the nature and frequency of medical error among junior doctors. Issue 1129 (24th July 2019) - O'Connor, Paul; Lydon, Sinéad; Mongan, Orla; Connolly, Fergal; Mcloughlin, Aoibheann; McVicker, Lyle; Byrne, Dara
Abstract: Purpose of the study: To examine junior doctors' experience and perceptions of medical errors in which they had been involved. Study design: A mixed-methods design, consisting of an error survey and critical incident technique (CIT) interviews, was used. The survey asked doctors in the first year of postgraduate training in Ireland whether they had made a medical error that had 'played on (their) mind', and if so, to identify factors that had contributed to the error. The participants in the CIT interviews were asked to describe a medical error in which they had been involved. Results: A total of 201 out of 332 (60.5%) respondents to the survey reported making an error that 'played on their mind'. 'Individual factors' were the most commonly identified group of factors (188/201; 93.5%), with 'high workload' (145/201; 72.1%) the most commonly identified contributory factor. Of the 28 CIT interviews which met the criteria for analysis, 'situational factors' (team, staff, task characteristics, and service user factors) were the most commonly identified group of contributory factors (24/28; 85.7%). A total of eight of the interviews were judged by subject matter experts (n=8) to be of medium risk to patients, and 20 to be of high-risk to patients. A significantly larger proportion of high-risk scenarios were attributed to 'local working conditions' than the medium-risk scenarios. Conclusions: There is a need to prepare junior doctors to manage, and cope with, medical error and to ensure that healthcare professionals are adequately supported throughout their careers.